Strategi Optimalisasi Mutual Legal Assistance (MLA) Untuk Pemulihan Aset Pada Kasus Tindak Pidana Pencucian Uang (TPPU) Transnasional - Pratama, Yudi Anugrah; Ervina Maharani Syahputri; Levia Komala Sari; Maria Ulfah; Kiki Amaliah (CV. ITTC INDONESIA, 2025)
This scientific work deeply examines the legal framework and operational challenges in optimizing the Mutual Legal Assistance (MLA) mechanism as a vital instrument for asset recovery stemming from cross-border Money Laundering Crimes (TPPU). The central issue investigated is the gap between the normative provisions of Law Number 1 of 2006 concerning MLA (UU MLA) and the reality of TPPU case handling which demands speed, efficiency, and adaptation to digital financial technology. Using a normative legal research method, this study highlights key obstacles including bureaucratic sluggishness of the diplomatic channel, the complexity of differing legal standards for evidence across jurisdictions, and the weakness in adopting the Non-Conviction Based Forfeiture (NCBF) mechanism in Indonesia, which is crucial for rapid asset seizure. The study findings indicate that while the UU MLA legally establishes the central authority, the asset recovery process is often hampered by the formalistic nature of criminal procedure law and the need for communication channels faster than conventional routes. Optimization is urgently required through strengthening domestic inter-agency coordination, adopting non-conviction based asset forfeiture, and utilizing international legal instruments such as the United Nations Convention Against Corruption (UNCAC) and informal networks like the Asset Recovery Inter-Agency Network (ARIN) to achieve economic justice and recover state losses to the treasury and victims.